2020
DOI: 10.1049/iet-cdt.2019.0086
|View full text |Cite
|
Sign up to set email alerts
|

VLSI implementation of anti‐notch lattice structure for identification of exon regions in Eukaryotic genes

Abstract: In a Eukaryotic gene, identification of exon regions is crucial for protein formation. The periodic-3 property of exon regions has been used for its identification. An anti-notch infinite impulse response (IIR) filter is mostly employed to recognise this periodic-3 property. The lattice structure realisation of anti-notch IIR filter requires less hardware over direct from-II structures. In this study, a hardware implementation of IIR anti-notch filter lattice structure is carried out on Zynq-series (Zybo board… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…It is found that quality ( ) and anti-notch frequency ( ) can be easily changed by adjusting the ANF lattice filter coefficients and , without altering each other. Hence, multiplier coefficients and can be independently adjusted for controlling the quality and anti-notch frequency of the ANF filter [21] .…”
Section: Rrm Model and Designing Of Bpn Filter For Characteristics Fr...mentioning
confidence: 99%
See 2 more Smart Citations
“…It is found that quality ( ) and anti-notch frequency ( ) can be easily changed by adjusting the ANF lattice filter coefficients and , without altering each other. Hence, multiplier coefficients and can be independently adjusted for controlling the quality and anti-notch frequency of the ANF filter [21] .…”
Section: Rrm Model and Designing Of Bpn Filter For Characteristics Fr...mentioning
confidence: 99%
“…BPN (ANF) IIR filter can be realized either by direct form or lattice structures whose Hardware architectures are explored in our previous work [21] , [29] , [30] , which were used for identification of exon regions in eukaryotic genes (different application). In this paper, lattice structures are followed due to the requirement of less logic hardware as compared to direct form structures, which are used for separate applications of hot-spots identification in SARS CoV2 proteins.…”
Section: Hardware Architecture Of Bpn Digital Lattice Iir Filter Syst...mentioning
confidence: 99%
See 1 more Smart Citation
“…In general, digital hardware outperforms and is more reliable than analog equipment, which can break down over time and have unpredictable results in the field [7]. Digital signal processing, on the other hand, provides a guarantee of accuracy and near-perfect repeatability [8]. There is a lot of interest in merging the various networks that communicate these signals [9].…”
Section: Introductionmentioning
confidence: 99%
“…High-speed FPGA (Sparten-6 and Virtex-7 series) implementation of various adaptive filter structures is carried out by Goel and Chandra 24 using retiming for speech enhancement through noise cancelation. Optimized VLSI implementation of direct form-II (DF-II) 25 and lattice structures 26 are explored for exon-region identification in eukaryotic genes. This paper is the extension of our previous conference paper 27 in which VLSI hardware implementation of tunable BPN digital filter for hot-spots localization in proteins is explored and which was not optimized for area and speed.…”
mentioning
confidence: 99%